Cost effectiveness analysis of the ready-to-use therapeutic food (RUTF) program for treating acute malnutrition children in Uganda - Aliakbarian, Manijeh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: This study is an ex-ante cost effectiveness analysis of a United States Agency for International Development (USAID) project for treating and preventing malnourished children in South Western Uganda. The results data used in the analysis in Acholi and Karamoja regions are for previous projects undertaken in the Uganda. For treating acute malnutrition uses Ready to Use Therapeutic Food (RUTF) as the major food for treating and preventing undernourishment children in Uganda .The costs of project include the cost of the therapeutic food (RUTF), the cost of the Health Center Visits, the cost of the Technical Assistance and Community Mobilization. The treatment method is outlined by Integrate Management of Acute Malnutrition (IMAM) guidelines Uganda ministry of Health, 2012.For measuring the effectiveness of the intervention in averting deaths we use the disability adjusted life year (DALY) calculated as a measure of mortality and morbidity. The cost per DALY saved is estimated using these parameters. A sensitivity analysis is also cleared out for the key variables. The cost effectiveness per DALY averted for the SPRING project is between US$ 26.28 and 38.98 per DALY saved. In the analysis of health costs in developing countries, this rate of cost effectiveness is considered quite low. It has been recommended by the World Bank that countries should implement all projects and programs that have a rate of cost effectiveness of less than $50.00 per DALY saved. This health intervention appears to be quite cost effective and should be implemented in Uganda. They key question is whether they will be able to obtain a sufficient volume of RUTF from the local supplier for the project. Keywords: Cost effectiveness analysis, disability adjusted life year (DALY), sensitivity analysis. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ:Bu çalışma Amerika Birleşik Devletleri Uluslararası Kalkınma Ajansı’nın Güney Batı Uganda’da besin yetmezliği nedeniyle zor durumda olan çocukların beslenmesi ve tedavisi için yürütülen projenin bir ön maliyet-fayda analizini oluşturmaktadır. Daha önceden Acholi ve Karamoja bölgelerinde yapılan çalışmaların sonuçları veri olarak dikkate alınmıştır. Akut beslenme yetersizliğinin tedavisinde temel besin maddesi olarak kullanıma hazır iyileştirici besin maddesi (RUTF) kullanılmıştır. Projenin maliyetleri, iyileştirici besin maddesi (RUTF), sağlık merkezi ziyaretleri, teknik yardım servisi maliyetleriyle toplum seferberliğinden oluşmaktadır. Tedavi yöntemi Akut Malnütrisyon Entegre Yönetimi şeklinde Uganda Sağlık Bakanlığı tarafından 2012 yılında belirlenmiştir. Ölümleri önlemeye yönelik müdahalenin etkinliğini ölçmek için Sakatlık Düzeltilmiş Yaşam Yılı (DALY) hesaplanmış böylece mortalite ve morbidite ölçülmüştür. DALY başına düşen maliyet tasarrufu bu parametreler kullanılarak hesaplanmıştır. Anahtar değişkenler için de bir duyarlılık analizi yapılmıştır. Ölümleri önlemede kullanılan Bahar Projesi’nin maliyet etkinliği DALY başına 26.28 ile 38.93 Amerikan Doları olarak hesaplanmıştır. Gelişmiş ülkeler için yürütülen sağlık maliyeti ile ilgili projelerde bu orandaki bir maliyet verimliliği düşük olarak kabul edilmektedir. Dünya Bankası tarafından tavsiye edilen yöntem bütün gerekli projelerin gelişmekte olan ülkeler tarafından hayata geçirilmesi ve maliyet etkinliğinin DALY başına 50 dolara çıkarılması yönündedir. Bu tarz bir ölümleri önleme projesi elbette ki Uganda için maliyet açısından etkin olacaktır. Anahtar soru ise projeye iyileştirici besini sağlayan üreticinin proje için yeterli miktarda tedariki (arzı) gerçekleştirip gerçekleştiremeyeceğidir. Anahtar Kelimeler: Maliyet Fayda Analizleri, Sakatlık Düzeltilmiş Yaşam Yılı (DALY), duyarlılık analizleri.
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2013. Supervisor: Prof. Dr. Glen Paul Jenkins.
Keywords: Economics; Cost effectiveness; Cost Effectiveness Analysis, Disability Adjusted Life Year (DALY), Sensitivity Analysis